Formulation Ointment Preparation Basil Essential Oil( Ocimum Basilicum L. ) Antibacterial Activity And TestON Staphylococcus Aureus - Rakhim, Mutia; , Dr. T.N. saifullah S., M.Si., Apt; , Ratna Yuliani, M. Biotech. St (2016)
Basil essential oil contains linalool compounds that capable of inhibiting the growth of Staphylococcus aureus. Essential oil is formulated in order to facilitate ointment application on the skin and prevent evaporation. This study was conducted to determine the physical properties, antibacterial activity and stability of basil essential oil ointment after 3 months storage. Basil essential oil was used as active compounds with concentration of 12.5%. Ointment with varying concentration of PEG 4000 : PEG 400 with ratio of 40%: 60% (F1), 30% : 70% w/v (F2), 20% : 80% (F3), and 10% : 90% (F4) were made. Ointment stability tests were conducted over 3 months includes organoleptic, pH, viscosity, spreadibility, adhesion, globules size, and freeze thaw for 6 cycles. Antibacterial activity test was conducted using well diffusion agar method. Data were analyzed by one-way ANOVA and Kruskal-Wallis. The results showed that the decrease of PEG 4000 and increase of PEG 400 decreased viscosity and adhesion, increased the spread but ointments pH were stable. Ointments that were storaged for 3 months have stable pH, lower adhesion and viscosity, but higher spreadibility than that of before storage. In the freeze thaw test, only F4 was unstable. Antibacterial activity of ointment against Staphylococcus aureus showed that ointment have greater inhibitory zones than the base, average ointment inhibitory zone is 21.49 mm.